A Humidity Compensation Method for On-line Odor Detection System in the Vehicle. Issue 4 (August 2020) - Cui, Chen; Liu, Wei; Wang, Lei; Liu, Xuefeng
Abstract: The paper introduce a humidity compensation method for the on-line detection system of odor in the vehicle. The method is based on theoretical model of dilution and humidity control, and the gas concentration of the sample to be measured under different dilution multiples is measured, and then the original gas concentration is calculated by linear fitting with the gas concentration data under the condition of low humidity, so that the humidity compensation of the measured sample gas can be carried out. After the humidity compensation method, the relative error of VOCs concentration of the sample A is about 15%, which is close to its real value, which significantly improves the accuracy of sample's VOCs concentration measurement.